PERLINDUNGAN HUKUM PEKERJA PERJANJIAN KERJA WAKTU TERTENTU (PKWT) YANG DI-PHK SEPIHAK SEBELUM MASA KONTRAK BERAKHIR: Legal Protection for Fixed-Term Employees (PKWT) Subject to Unilateral Termination Before Contract Expiration - Syakirah Dena Salsabilah; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2026)
Legal protection for Fixed-Term Employment Agreement (PKWT) workers is often vulnerable, especially in cases of unilateral Termination of Employment (PHK). This study aims to examine the legal protection for PKWT workers subject to unilateral PHK in Decision Number 361 K/Pdt.Sus-PHI/2024. The legal problem stems from the dispute between Aprianti Amir and KKB Selindo, where termination occurred citing failure to meet work targets. This research was conducted using the Normative Legal Research method, which is Descriptive Analytical, sourced from secondary data analyzed qualitatively so that conclusions can be drawn deductively. The result is normative protection is governed by the obligation to pay PKWT compensation (Article 17 GR 35/2021) and contract remainder indemnity (Article 62 Law 13/2003) if the termination is not due to the worker's fault. The PHI granted full rights, but the Supreme Court (MA) at the cassation level classified the inability to meet targets as